Clinical mycology - Dismukes, William E.; Pappas, Peter G.; Sobel, Jack D. (Oxford University Press, 2003)
Within the field of infectious diseases, medical mycology has experienced significant growth over the last decade. Invasive fungal infections have been increasing in many patient populations, including: those with AIDS; transplant recipients; and the elderly. As these populations grow, so does the diversity of fungal pathogens. Paralleling this development, there have been recent launches of several new antifungal drugs and therapies. Clinical Mycology offers a comprehensive review of this discipline. Organized by types of fungi, this volume covers microbiologic, epidemiologic and demographic aspects of fungal infections as well as diagnostic, clinical, therapeutic, and preventive approaches. Special patient populations are also detailed.